(3QSGdI GdJhMjOs - (3eMeO Hf eMeO Hf eMehO GdHNGQj GdMfaj, TeS GdOjf,J (B850 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd CabQ GdYHOGf eMeO Hf eMeO Hf eMehO GdoHNGQj deG cGf GdCfLH hGdChLH Ydi GdCfS hGdLGf JhMjO ef JbOS s
(3BNQgG (B:s
(3hEf CHWf YbGFO gj caQ haGboG JeJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B299 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B196s
(3eUOQ GbJfGA GdCUd (B:s
(3HdOjI GdCScfOQjI (B(3182 (3L(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds